Measuring EFL Students' Motivation in Academic Writing Through the Use of ChatGPT - Astriana Talango; Nonny Basalama; Dewi Dama (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
The increasing use of artificial intelligence (AI) tools such as ChatGPT has transformed students’ academic writing practices. While ChatGPT offers various forms of writing assistance, its relationship with students’ motivation to write remains a subject of debate. Therefore, this study aimed to examine the relationship between ChatGPT usage and academic writing motivation among EFL students at Universitas Negeri Gorontalo. Grounded in Self-Determination Theory (Ryan & Deci, 2000; 2020), this study employed a quantitative correlational design involving 100 fourth-semester students selected through purposive sampling. Data were collected using the Academic Writing Motivation Questionnaire (AWMQ) adapted from Payne (2012) and the ChatGPT Usage Scale adapted from Nemt-allah et al. (2024). The data were analyzed using Pearson Product-Moment Correlation after meeting the assumption of normality. The findings revealed that the participants demonstrated a moderate level of academic writing motivation. Furthermore, a statistically significant negative correlation was found between ChatGPT usage and academic writing motivation (r = −.244, p = .015). This indicates that students who reported more frequent use of ChatGPT tended to exhibit lower levels of motivation in academic writing, although the strength of the relationship was weak. Since this study adopted a correlational design, no causal relationship can be established. These findings suggest that the use of ChatGPT may be associated with changes in students’ motivation toward academic writing and highlight the importance of promoting balanced and responsible use of AI tools in educational contexts.